USULAN WAKTU PERAWATAN DAN PERBAIKAN BERDASARKAN KEANDALAN PADA BAGIAN BOILER DI PEMBANGKIT LISTRIK TENAGA UAP - Pamungkas, Iing; Irawan, Heri Tri; Arhami, Arhami; Dirhamsyah, Muhammad (Universitas Teuku Umar, 2019)
PT. PLN (Persero) is the sole manager of the electricity industry in Indonesia which is owned by the Indonesian government in the form of a State-Owned Enterprise. Steam power plant is one of the leading power plants in Indonesia. Aceh Province has one steam power plant located in Nagan Raya Regency and has two generating units with an installed capacity of 2x110 Megawatts. However, a power outage is unavoidable and still often occurs if one of the plants is damaged or damaged. Corrective maintenance activities and overall maintenance is one of the causes of the high frequency of interference or damage, especially in the boiler section. This study aims to determine the proposed maintenance and repair time to achieve a reliability level of up to 80% in every important boiler component. The proposed maintenance and repair time can be obtained based on historical time to failure and time to repair data. Good maintenance and repair time can be assessed based on high reliability values. The results obtained that the proposed maintenance time is 67 hours to 585 hours to achieve 80% reliability value on eight important components in the boiler section. While the proposed repair time is from 1,036 hours to 1,497 hours to reach 80% reliability value on eight important components in the boiler section.